Answers

2014-10-07T20:02:01+08:00
Since it is varied jointly then we can say that it is directly proportional that when you increase any of the base or height, the area will increase.
Disregarding the formula for the triangle and having it as an equation of joint variation then you'll have
A = kbh
where A is the area, b is the base length, h is the height/altitude and k is the constant. 
Substituting you'll have:
A =kbh
65 = k(10)(13)
k = 65/130
k = 1/2
For the given b=8cm, h=11cm you'll have
A = kbh
A = (1/2)(8)(11)
A = 44 cm²
1 5 1